Anchoring of a Kinked Uncemented Femoral Stem after Preparation with a Straight or a Kinked Reamer. Issue 4 (22nd July 2019) - Heinecke, Markus; Layher, Frank; Matziolis, Georg
Abstract : Objective: To investigate a stem‐adjusted preparation of the femur with a kinked reamer and to determine whether this approach results in higher primary stability of a kinked stem than straight reaming of the intramedullary canal. Methods: Ten cementless stems with a kinked design were implanted in synthetic femurs after preparation of the femoral canal with 2 different reamer designs (straight reaming [SR] group vs kinked reaming [KR] group). The specimens were analyzed using CT to determine the anchoring length and examined with a mechanical testing system to establish their axial stiffness, torsional stiffness, and migration distance after 10 000 gait cycles. Results: The stem migration distances did not differ significantly between the groups (SR group 0.51 ± 0.16 mm vs KR group 0.36 ± 0.03 mm, P = 0.095). Only for the SR group, a correlation was found between the completely conical anchorage length and absolute stem migration ( P < 0.05, R = 0.89). Regarding the torsional stiffness, no differences were observed between the study groups (SR group 6.48 ± 0.17 Nm/° vs KR group 6.52 ± 0.25 Nm/°, P = 0.398). In the KR group, significantly higher axial stiffness values were measured than in the SR group (SR group 1.68 ± 0.14 kN/mm vs KR group 2.09 ± 0.13 kN/mm, P = 0.008). Conclusions: The implantation of a kinked stem after kinked conical intramedullary preparation of the proximal femur showed equivalent results regarding anchoring length, stem migration, and torsional stiffness to those for straight conical reaming. The specimens with kinked reaming showed significantly higher axial stiffness values.